2020
DOI: 10.1096/fj.202001466r
|View full text |Cite
|
Sign up to set email alerts
|

Conspicuity of prostate cancer on multiparametric magnetic resonance imaging: A cross‐disciplinary translational hypothesis

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Similarly, PI-RADS could be used as another means of assuring the patient that active surveillance is the treatment of choice, in patients with neglectable risk of distant failure. The score most likely goes beyond the standard risk assessment through significant association with routinely non-reported histopathological hallmarks [ 24 ] and genomic changes [ 25 , 26 , 27 , 28 ]. Moreover, the PI-RADS score of 5 and large axial measurements of the target lesion found in low or intermediate-risk group PCa patients could be an important predictive factor for the necessity of secondary pre-treatment biopsy or early confirmatory biopsy in patients opting for active surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, PI-RADS could be used as another means of assuring the patient that active surveillance is the treatment of choice, in patients with neglectable risk of distant failure. The score most likely goes beyond the standard risk assessment through significant association with routinely non-reported histopathological hallmarks [ 24 ] and genomic changes [ 25 , 26 , 27 , 28 ]. Moreover, the PI-RADS score of 5 and large axial measurements of the target lesion found in low or intermediate-risk group PCa patients could be an important predictive factor for the necessity of secondary pre-treatment biopsy or early confirmatory biopsy in patients opting for active surveillance.…”
Section: Discussionmentioning
confidence: 99%
“…Much less is known about the added value of MRI lesion features (PI-RADS/Likert) as an independent prognostic or predictor of outcome. Lesions visibility is being explored by different groups with so far inconclusive results [ 38 , 39 ]. In a review of the literature Stabile et alfound 6 studies on the predictive role of the PI-RADS score and concluded that reliable evidence was limited but there was a trend for better prediction of biochemical relapse after surgery [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 There is also increasing evidence to suggest that mpMRI-visible lesions may associate with more aggressive clinical features. 8 Given this growing body of evidence linking risk, location and conspicuity on mpMRI, the Open access need to amalgamate these features is evident. Therefore, the objective of this systematic review and meta-analysis is to collate the extant evidence regarding the effect of prostate cancer zonal location on mpMRI conspicuity, for the first time.…”
Section: Introductionmentioning
confidence: 99%